Thewithdrawal of consent to haematopoietic stem cells (HSC) donation: The complicated balance between donor's rights and patient's protection. (August 2020) - Iuliani, O.; Passeri, C.; Papola, F.; Accorsi, P.
Abstract: Hematopoietic stem cells donation is an essential prerequisite of allogeneic transplantation. Both family donors and matched unrelated donors should have a conscious involvement in every phase of the overall path, from selection to HSC collection. Donors also should be informed about the right to withdraw at any time as well as the extreme risk for recipient's life coming from the decision of interrupting, if the donation is not carried out once the patient's preparative regimen has commenced. We report our challenging experience about a donor who withdraws her consent to HSC donation after 3 days of mobilization with G-CSF. The possibility of withdrawal protects the donor but it also puts at risk both a chance for a transplant and the patient's life if preparative regimen has started. Can the donor really be free to withdraw the consent to HSC donation at any time even when this endangers the life of a recipient? Is this ethical? However, if the donor decides to withdraw, would we really be ready to manage promptly all the consequences coming from the consent revocation? At the moment there is not a well-defined "plan B" in case of impossibility to proceed with the transplant when conditioning has already started or has even been completed. In our opinion, because of this hard balance and such a high risk, it would be necessary to plan every time an alternative strategy which may be different according to different circumstances.